Integration of Islamic Values and Local Knowledge in Social Practices for Environmental Conservation in Banjaranyar - Antoni, Muhamad Rizal; Brata, Yat Rospia; Sudarto, Sudarto (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
The study examines the integration of Islamic values and local knowledge in environmental conservation practices in Banjaranyar. The study aims to reveal how these two sources of values complement each other in promoting environmental awareness and conservation actions by the local community. Qualitative methods with a descriptive approach were used, including observation, interviews, and documentation studies. The findings show that there's harmony between Islamic principles, like the caliph's responsibility on earth, and local wisdom in managing natural resources in a sustainable way. This integration creates effective social practices in maintaining ecosystem balance and strengthening the cultural identity of the Banjaranyar community. The research has important implications for developing environmental conservation models based on religious and local cultural values that can be adapted in other areas.